The Effect of Fusion Added to Lumbar Discectomy in Patients with Modic Changes: A Retrospective Comparative Outcome Analysis Regarding Back Pain Control - Ahmad Elsayed Desoukey Elayouty, MD., (Egyptian Spine Association, 2018)
Background Data: In 1988, Modic et al first described magnetic resonance (MR) degenerative changes in the lumbar vertebral bodies. changes in the intervertebral endplates, Modic Changes (MC) can also be incriminated in the production of such pain due to the mechanical failure and structural changes that can be detected the most in the region of the highly pain sensitive intervertebral endplates. There is still a controversy regarding the surgical treatment of the predominantly axial pain secondary to degenerative lumbar disc disease. Study Design: This is a retrospective cohort study. Purpose: To evaluate the effect of adding fusion to simple discectomy in treatment of patients of lumbar disc herniation that show evidence of MC on preoperative MR images regarding the control of postoperative back pain and functional outcome. Patients and Methods: This study included 44 patients who underwent surgical management of low back pain and/or sciatica due to lumbar intervertebral disc herniation with concomitant presence of Modic changes in the preoperative MR images. Patients were divided into two groups: Group A (Discectomy group), and Group B (Fusion group). Patients included had single level lumbar disc herniation with modic changes. Patients with radiographic evidence of instability and patients whose 1-year post-operative data were incomplete were excluded. Twenty five patients were males and 19 were females with a mean age of 43.48 years. Nineteen patients (43.2%) were allocated in Group A and 25 patients (56.8 %) in Group B. Clinical results and functional outcome were assessed based on changes in preoperative and postoperative Visual Analogue Scale (VAS) of low back pain and Oswestry Disability Index (ODI) scores of the functional disability. Results: Postoperative back pain improvement was statistically significant in both groups when comparing preoperative values of VAS using paired student-t test with P<0.001 for both groups. Comparison of post-operative back pain VAS for both groups using independent student-t test revealed a statistically non-significant difference with a P=0.239 (Mean VAS for group A=2.211 while mean VAS for Group B=1.48). Conclusion: Unless otherwise indicated, simple lumbar discectomy without fusion is a reasonable surgical option in treatment of patients with lumbar intervertebral disc herniation even in the presence of Modic changes in their pre-operative MRI. (2018ESJ167)